Persepsi Nilai Sebagai Pemoderasi Dimensi Kualitas Pelayanan dan Loyalitas Nasabah Perbankan Syariah di Daerah Istimewa Yogyakarta - Yanti, Sur; Prayitno, Edy (Graduasi: Jurnal Bisnis & Ekonomi, 2014)
Islamic banking to function as a financial intermediary that support the development process. Operational activities of Islamic banking is managing investment funds and deposits are sources of funding and managing social as zakat, infaq, alms, and waqaf. Increased competition due to the liberalization of the domestic banking system that makes international banks into Indonesia and lead to a larger market, so customers have more choices to determine who will be selected banking institutions. Lack of understanding of the definition of service quality in the banking industry is considered one of the obstacles to successful implementation of quality initiatives in the banking sector (Nielson and Host, 2000). Seeing the importance of retaining customers due to increased competition in the banking sector, the researcher analyzed the service quality dimensions Islamic Bank in Yogyakarta and customer satisfaction on customer loyalty with customer perceived value variables against Islamic Bank as a moderating factor, by developing a model of the previous research. Model evaluation Partial Least Square (PLS) based on the measurement of the non-parametric prediction have used in this study. The results of this study is the construct of service quality dimensions of service quality dimensions 1 and 2 related positively and significantly to the Islamic banking customer satisfaction. Likewise construct customer satisfaction positively and significantly related to Islamic banking customer loyalty. While constucs customer perceived value as a moderating between the construct of customer satisfaction with the level of customer loyalty Islamic banking is not significant. With the results of these studies can be used managers of Islamic banks as a measure to assess the factors that can improve customer satisfaction, thereby increasing customer loyalty to the Islamic banking in Yogyakarta